Influence of the representation of the distribution transformer core configuration on voltages developed during unbalanced operations - Vernieri, Julieta Z. (2001)
The object of this paper is to emphasize the importance of the representation of the core configuration when seeking transients developed in a distribution transformer under an unbalanced situation. Digital time-domain simulations are performed with the Alternative Transients Program (ATP) for the case of a distribution three-phase transformer using the following two core configuration representations available in the ATP: three-legged core form and fivelegged core. Severe overvoltages and high saturated currents would not be evidenced if the wrong core configuration representation was used during simulations.